Using the plan–do–study–act (PDSA) cycle to make change in general practice - Crowfoot, Daniel; Prasad, Vibhore (SAGE, 2017)
As new members of the team, GP trainees can provide a fresh perspective on practice systems. They are, therefore, ideally placed to enact change within practices. However, GP trainees may feel ill-equipped to suggest and deliver change to their practices. This article will explore the concept of change management using the plan–do–study–act cycle and consider how to initiate change by providing a structure to guide the process.